Slovenščina na dlani 4 (University of Maribor Press, 2021)
Slovene in the Palm of Your Hand 4. The monograph presents scientific papers (the first part of the monograph) and professional papers (the second part) concerning the development and use of language resources as well as e-learning environments for Slovene language teaching. It sets out from the perspective of digitalisation in linguistics and novel Slovene teaching possibilities, while indicating guidelines for the development of learning materials. The present work highlights the newest language resources that facilitate Slovene learning and teaching, e.g., Vejice 1.0, Jezikovni sledilnik 1.0, Sloleks 2.0, SPiPP, some of which also efficiently employ gamification elements, e.g., Igra besed. The focus of interest is the innovative e-learning environment Slovenščina na dlani (Slovene in the Palm of your Hand) with its construction and the specifics of its thematic components. Moreover, the present work analyses the effect of informational literature in e-learning environments on reading literacy development. The monograph is rounded off with reflection on the significance of multilingualism and personal plurilingualism in the digital age, as well as an illustration of the innovative didactic approaches that arose due to the increased use of modern technologies due to the epidemiological situation.